Amino acid digestibility of protein and energy ingredients of plant origin in bullfrog (Lithobates catesbeianus) - Menegasso Mansano, Cleber Fernando; Macente, Beatrice Ingrid; Torres do Nascimento, Thiago Matias [UNESP]; Pereira, Marcelo Maia; Khan, Kifayat Ullah [UNESP]; da Silva, Edney Pereira [UNESP]; Takahashi, Leonardo Sussumu [UNESP]; de Stéfani, Marta Verardino [UNESP] (Elsevier, 2020)
Due to increasing demand of ingredients of animal origin, studies on the availability of nutrients in ingredients of plant origin are worthy in carnivorous species including bullfrog. This study aimed to determine apparent digestibility coefficients (ADCs) of amino acids (AAs) in three ingredients as plant protein sources (soybean protein concentrate (SPC), corn gluten meal 60 % (CGM), soybean meal (SM)) and two ingredients as plant energy sources (corn grain (CG) and wheat bran (WB)) which commonly use in bullfrog diets. A reference diet and five test diets containing 69.5 % of the reference diet, 30 % of each test ingredient and 0.5 % of chromium (III) oxide as an inert marker were prepared. Among plant protein ingredients, CGM showed better digestibility of essential amino acids (EAAs) (> 80 %) at the three post-metamorphic (initial, growing and finishing) phases of bullfrog development, except tryptophan which presented a low digestibility at growing and finishing phases. Among plant energy ingredients, CG presented better digestibility of AAs at both initial and growing phases than WB which showed better digestibility only at finishing phase. It was observed that methionine and lysine are the most limiting EAAs in tested ingredients, indicating that additional amounts of these AAs should be supplemented when these ingredients are used in bullfrog diets.
Keywords: Amphibians; Apparent digestibility coefficients; Feed formulation; Nutrient availability; Plant ingredients